Bioinspired Synthesis of Pulvinic Acids Including Xerocomic Acid and Fluorescence Properties of Bis‐lactone Intermediates. Issue 8 (11th January 2023) - Pradayrol, Élodie; Séon‐Méniel, Blandine; Oger, Samuel; Sinniah‐Kandiah, Biraveena; Guillot, Régis; Franco, Rémi; Souce, Martin; Kasselouri, Athéna; Maciuk, Alexandre; Evanno, Laurent
Abstract: A set of representative pulvinic acids were synthesised using a bioinspired strategy. Terphenyl‐quinones (polyporic acid scaffold) were prepared via sequential Suzuki‐Miyaura couplings allowing access to unsymmetrically substituted derivatives in a one‐pot protocol. Subjected to the action of acetic anhydride and DMSO, quinones were converted into bis‐lactone intermediates. Methanolysis and deprotection achieved the total syntheses of the corresponding pulvinic acids. Following this general strategy, symmetrical pulvinic, atromentic, variegatic acids and unsymmetrical congener pinastric, iso‐pinastric, xerocomic and iso‐xerocomic acids were prepared in fair yields. Fluorescence properties were observed for the bis‐lactone intermediates and, as a complement to this synthetic work, optical properties were measured, and fluorescence quantum yields were determined for the bis‐lactone pigments. Abstract : Six pulvinic acids (pulvinic, pinastric, atromentic, xerocomic, isoxerocomic, variegatic) and a polyporic acid (atromentin) were synthesised. A set of terphenyl‐quinones was prepared through sequential Suzuki‐Miyaura couplings. Then, a rearrangement into pulvinic bis‐lactones was induced by the action of Ac2 O/DMSO. Ring openings and deprotections achieved total syntheses. Fluorescence properties of bis‐lactones were determined.